Discovery of the Hedgehog Pathway Inhibitor Pipinib that Targets PI4KIIIß. (4th October 2019) - Kremer, Lea; Hennes, Elisabeth; Brause, Alexandra; Ursu, Andrei; Robke, Lucas; Matsubayashi, Hideaki T.; Nihongaki, Yuta; Flegel, Jana; Mejdrová, Ivana; Eickhoff, Jan; Baumann, Matthias; Nencka, Radim; et al.
Abstract: The Hedgehog (Hh) signaling pathway is crucial for vertebrate embryonic development, tissue homeostasis and regeneration. Hh signaling is upregulated in basal cell carcinoma and medulloblastoma and Hh pathway inhibitors targeting the Smoothened (SMO) protein are in clinical use. However, the signaling cascade is incompletely understood and novel druggable proteins in the pathway are in high demand. We describe the discovery of the Hh‐pathway modulator Pipinib by means of cell‐based screening. Target identification and validation revealed that Pipinib selectively inhibits phosphatidylinositol 4‐kinase IIIβ (PI4KB) and suppresses GLI‐mediated transcription and Hh target gene expression by impairing SMO translocation to the cilium. Therefore, inhibition of PI4KB and, consequently, reduction in phosphatidyl‐4‐phosphate levels may be considered an alternative approach to inhibit SMO function and thus, Hedgehog signaling. Abstract : Zell‐basiertes Screening führt zur Identifizierung eines Thieno[3, 2]pyrimidin‐Derivats als Inhibitor des Hedgehog‐Signalwegs, welches selektiv die Phosphatidylinositol‐4‐Kinase IIIβ (PI4KB) inhibiert, die PI4P‐Menge reduziert und die Hedgehog‐vermittelte ziliäre Lokalisation von Smoothened verhindert. Daher könnte PI4KB ein relevantes Zielprotein zur Inhibierung des Hedgehog‐Signalwegs sein.